Charles W. Sandford correspondence - Sandford, Charles W.
ALS written by Sandford to Gen. Sylvester Churchill relating to plans for a Fourth of July celebration in New York, N.Y.
Army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Churchill, Sylvester, -- 1783-1862 -- Correspondence; Fourth of July -- New York (State) -- New York; Army officers